Norfluoxetine inhibits TREK-2 K2P channels by multiple mechanisms including state-independent effects on the selectivity filter gate - Proks, P; Schewe, M; Conrad, LJ; Rao, S; Rathje, K; Rödström, KEJ; Carpenter, EP; Baukrowitz, T; Tucker, SJ (Rockefeller University Press, 2021)
The TREK subfamily of two-pore domain K+ (K2P) channels are inhibited by fluoxetine and its metabolite, norfluoxetine (NFx). Although not the principal targets of this antidepressant, TREK channel inhibition by NFx has provided important insights into the conformational changes associated with channel gating and highlighted the role of the selectivity filter in this process. However, despite the availability of TREK-2 crystal structures with NFx bound, the precise mechanisms underlying NFx inhibition remain elusive. NFx has previously been proposed to be a state-dependent inhibitor, but its binding site suggests many possible ways in which this positively charged drug might inhibit channel activity. Here we show that NFx exerts multiple effects on single-channel behavior that influence both the open and closed states of the channel and that the channel can become highly activated by 2-APB while remaining in the down conformation. We also show that the inhibitory effects of NFx are unrelated to its positive charge but can be influenced by agonists which alter filter stability, such as ML335, as well as by an intrinsic voltage-dependent gating process within the filter. NFx therefore not only inhibits channel activity by altering the equilibrium between up and down conformations but also can directly influence filter gating. These results provide further insight into the complex allosteric mechanisms that modulate filter gating in TREK K2P channels and highlight the different ways in which filter gating can be regulated to permit polymodal regulation.